2018
DOI: 10.1016/j.maturitas.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of a single-arm pilot study to assess the safety and efficacy of visnadine, prenylflavonoids and bovine colostrum in postmenopausal sexually active women affected by vulvovaginal atrophy

Abstract: This single-arm pilot study enrolled 47 post-menopausal women affected by vulvovaginal atrophy (VVA). The Vaginal Health Index Score (VHIS) was evaluated for all women and all completed the Female Sexual Function Index (FSFI) questionnaire at baseline (T0) and after 15 days of vaginal cream treatment with one application per day (T1). Following treatment there was a significant improvement in all VHIS parameters and total score (p < 0.0001). Similarly, there was a significant improvement on four FSFI domains (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…Although menopause is a normal and natural physiological process in a woman's life, it can negatively affect [2,3] the one-third of their lifetime after menopause [4]. Studies have shown the negative impacts of menopausal symptoms on health-related quality of life (HRQOL) [5][6][7][8][9]. Almost all women experience multiple symptoms, such as hot flushes, sweats, sleep disorders, depression, and vaginal dryness.…”
Section: Introductionmentioning
confidence: 99%
“…Although menopause is a normal and natural physiological process in a woman's life, it can negatively affect [2,3] the one-third of their lifetime after menopause [4]. Studies have shown the negative impacts of menopausal symptoms on health-related quality of life (HRQOL) [5][6][7][8][9]. Almost all women experience multiple symptoms, such as hot flushes, sweats, sleep disorders, depression, and vaginal dryness.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that between 15% and 25% of gynecologists in the United States perform office hysteroscopy and, thanks to an easy-to-improve learning curve, the amount of young and senior operators is still increasing [6]. Nonetheless, hysteroscopy plays a crucial role in the most challenging topics of women's health, from infertility diagnostic work-up [7,8] to post-menopausal abnormal uterine bleeding and uterine pathologies [9,10]. Currently, available technologies allow one to perform several diagnostic and operative procedures without the need for anesthesia and without any pain or distress for the patient [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…40 Management strategies should include empowering women to participate in their care that will improve their sense of control and overall care, 41,42 together with exercise and diet recommendations, including isoflavones, calcium and vitamin D which may have favorable effects on menopausal symptoms and quality of life 43 and sexual health. 44 The gold standard treatment for women that seek control of their symptoms is hormone replacement therapy (HRT), but the optimal course of treatment is unclear due to mixed results from studies. 45,46 Initial interpretation of the Women's Health Initiative in the early 2000s saw a rapid decrease in HRT use, though current thinking appears to show that women under the age of 60 at the onset of menopause have a favorable risk-benefit profile when taking HRT for short-term relief of vasomotor symptoms.…”
Section: Resultsmentioning
confidence: 99%